If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7 = 3(2x + 1) Reorder the terms: -7 + x = 3(2x + 1) Reorder the terms: -7 + x = 3(1 + 2x) -7 + x = (1 * 3 + 2x * 3) -7 + x = (3 + 6x) Solving -7 + x = 3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -7 + x + -6x = 3 + 6x + -6x Combine like terms: x + -6x = -5x -7 + -5x = 3 + 6x + -6x Combine like terms: 6x + -6x = 0 -7 + -5x = 3 + 0 -7 + -5x = 3 Add '7' to each side of the equation. -7 + 7 + -5x = 3 + 7 Combine like terms: -7 + 7 = 0 0 + -5x = 3 + 7 -5x = 3 + 7 Combine like terms: 3 + 7 = 10 -5x = 10 Divide each side by '-5'. x = -2 Simplifying x = -2
| 6/52x6/51 | | 2x+6=6x-1 | | y=3x^3-27x^2+24 | | 24/2=x/5 | | (X^2)+81=0 | | 5/7x-4/3=(3x+1)/2 | | 4(x-7)=11 | | 6/5x+2x=17 | | -3y-3y=-15 | | (4x+3)(4x+3)=225 | | n/4-8=-5 | | -3.5x=58.10 | | 35=n-(-16) | | 2y(x+4)=144y | | -(5x+3)-4=8+6x | | 8h+4=2h-20 | | jh=5 | | 4r^2=9/16 | | 0.70x+0.45(30)=56.9 | | (35x^3-6x)/7x | | 1/2x+5=3x-4 | | 16c^2+24c+9=0 | | 18/-6= | | -125=-5(5+4x) | | .5x+5=3x-4 | | (x+2)/(x+6)=1/3 | | 8x+3(20-x)=5(20) | | -8/7r+4r=1/4r+73/4 | | 5(5m-7)+2=-83 | | 8x+3(20)=5(x+20) | | 2(8p+7)=94 | | q^2+20q+19=0 |